2012
DOI: 10.1007/s13337-012-0113-0
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus Manipulates Ubiquitin Gene Expression in Penaeus monodon

Abstract: The present study reports the effect of WSSV on the expression profiles of shrimp ubiquitin gene both at protein and transcript levels at different time points after infection. A gradual decrease in ubiquitin protein levels was observed till 12 hpi (0.25 and 0.23 lg/mg of the total protein in gills and muscle, respectively) with a sudden increase at 18 hpi (1.86 and 1.8 lg/mg of total protein in gills and muscle, respectively). The RT-PCR results showed a gradual decrease in ubiquitin mRNA levels in gill tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…This pathway also participated in viral infection and assists activities required of different aspect of virus life cycle, such as entry, replication and shedding [ 94 ]. Recently, various reports have been conducted showing the hijack of UPP pathway to regulate cellular intrinsic antiviral activities and innate immunity induced by WSSV [ 95 , 96 ]. E3 ubiquitin-protein ligase HUWE1 with the highest up changes after WSSV chanllenge was found in M .…”
Section: Discussionmentioning
confidence: 99%
“…This pathway also participated in viral infection and assists activities required of different aspect of virus life cycle, such as entry, replication and shedding [ 94 ]. Recently, various reports have been conducted showing the hijack of UPP pathway to regulate cellular intrinsic antiviral activities and innate immunity induced by WSSV [ 95 , 96 ]. E3 ubiquitin-protein ligase HUWE1 with the highest up changes after WSSV chanllenge was found in M .…”
Section: Discussionmentioning
confidence: 99%
“…As for the Hsp40 gene, its responses to viral infection have been reported in halibut Paralichthys olivaceus [55]. In another study using the WSSV challenged tiger shrimp P. monodon, ubiquitin gene was down-regulated during the first 12 hours, but reversed in the following period [56]. Lastly, a study in red swamp crayfish, Procambarus clarkii, listed DnaJ (Hsp40), ubiquitin, and innexin (detailed below) proteins for their possible anti-WSSV roles [57].…”
Section: Nimav-1_lva Genes Involved In Host-pathogen Interactionmentioning
confidence: 93%
“…Our results also showed that levels of ubiquitin transcripts varied depending on the WSSV post-infection time interval, as well as the viral load, both in cabs and shrimp. Vidya et al (2013) suggested that one of the viral strategies to keep progressive infection involves modifying host ubiquitination.…”
Section: Differential Expression In N Granulata and L Vannamei Relate...mentioning
confidence: 99%